Evaluation of three pour on commercial formulations under field conditions and their in vitro effect on the control of Boophilus microplus (Acari: Ixodidae) in cattle in tropical lowlands - del Castillo L., del Castillo L. (2016)
The aim of this study was to evaluate three pour on commercial formulations under field and in vitro conditions on the control of Rhipicephalus (Boophilus) microplus in naturally infested cattle in Oxapampa, Peru. For the field evaluation 105 cattle having 30 or more engorged female ticks in one flank were selected and equally distributed in three groups of 35 animal each: Fipronil 1% + Abamectin 0.5% + Neem Oil 2% (FAN), Flumethrin 1% + Eprinomectin 0.5% (FE), and Flumethrin 1% + Fluazuron 2.5% (FF). All animals were treated with 1 ml/10 kg bw via pour on the dorsal line. The number of >4.5 mm engorged female was counted on days 0, 7, 14, 21, 28, and 56 post-treatment. Effectiveness was evaluated by the Teleogines Count Reduction Test. For the in vitro study 50 teleogines (160-340 mg) were collected per group at 24, 48, and 72 h post-treatment, as well as from a separate group without treatment. Thirty ticks of similar weights (160-340 mg) per group were immobilized with adhesive tape and incubated at 27 ºC and 85% relative humidity during 21 days. Mortality and oviposition were evaluated. The eggs were incubated during 30 days to determine larval hatching, reproductive efficiency and in vitro effectiveness. The field study showed that FAN (99.4-100%), FE (95.8-98.4%), and FF (97.3-98.8%) had adequate efficacy (>95%) on days 7 to 28, 7 to 14 and 21 to 56, respectively. In the in vitro evaluation only FAN and FF showed 100% efficacy on engorged female collected at 24, 48, and 72 h post-treatment, while FE showed an efficacy of 98-99% on engorged female collected at 48 and 72 h post-treatment.